Tracking Fatty Acids From Phytoplankton to Jellyfish Polyps Under Different Stress Regimes: A Three Trophic Levels Experiment - Chi, Xupeng; Javidpour, Jamileh; Sommer, Ulrich; Mueller-Navarra, Doerthe (Frontiers in Ecology and Evolution, 2018)
The impacts of biochemicals driving food web processes are under investigation for just the last few decades. In addition, as jellyfish are drawing increasing attentions because of their mass developments and of their potential capacity of driving food web structures and energy flow by ‘top-down’ and ‘bottom-up’ controls. We here show that the provision with the biochemical complex thiamin (vitamin B1) to the common phytoplankton Rhodomonas baltica altered its fatty acid (FA) pattern towards 3-highly-unsaturated FAs (3-HUFA) and that this pattern was further transferred up to the zooplankton consumer, the copepod Acartia tonsa. However, polyps of the Jellyfish Aurelia aurita feeding on A. tonsa only had a low relative 3-HUFA content, especially due to a reduction in 22:63 (DHA), but elevated levels of 20:46 (ARA). The high proportion of the -6 HUFA, ARA in polyps may provide evidence for preferential conversion of ARA in polyps, eventually from DHA in a so far unknown pathway. In contrast to A. tonsa, newly hatched A. salina nauplii used as food for A. aurita polyps were almost devoid of HUFA, but contained high levels of C18 polyunsaturated FAs (C18-PUFA). Consequently, polyps feeding on them contained few HUFA, while high levels of C18-PUFA predominated. This suggests that A. aurita polyps cannot efficiently convert 3 C18-PUFA to 3-HUFA. In addition, besides a decrease in saturated FAs, especially an increase in HUFA in A. aurita polyps with decreasing temperature was observed, for which the dietary provision with HUFA seemed to be critical. Altering the FA pattern as a response of temperature reflects an adaptation to seasonal changes and may be related to their life history plasticity.